Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation untuk Meningkatkan Hasil Belajar Siswa Kelas X SMAN 6 Kendari Pada Materi Langkah Langkah Penelitian Geografi - La Ode Ramadan Abubakar; Sitti Kasmiati; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
The learning outcomes of class X students of Senior High School 6 Kendari still relatively low. This is because teachers still apply conventional learning models. The objectives of this study were: 1) to determine the significance of the difference in the average pre-test scores of experimental class students and the average pre-test scores of control class students on the Geography Research Steps material, and 2) to determine the average post-test scores of experimental class students and the average post-test scores of control class students on the Geography Research Steps material. The type of research used was an experiment with the Pre-test Post-test Group Design method. Data were analyzed using descriptive analysis and inferential analysis. Based on the data analysis, the following conclusions were obtained: 1) the average learning outcomes of the experimental class were obtained pre-test 41.38 and post-test 83.61 and the average learning outcomes of the control class were obtained pre-test 45.83 and post-test 74.30; 2) there is no significant difference in the average pre-test scores of students in the experimental class and control class with the results of the Independent Sample T-Test showing that the t value = 0.72> 0.05 which means there is no significant difference with a significance level of 0.05, 3) the average post-test learning outcomes of the experimental class are significantly better than the average post-test scores in the control class with the results of the Independent Sample T-Test showing that the t value = 0.01 < 0.05 which means there is a significant difference.